Cryptococcal immune reconstitution inflammatory syndrome after antiretroviral therapy in AIDS patients with cryptococcal meningitis: A prospective multicenter study - Somnuek Sungkanuparph (2018)
A prospective multicenter study of cryptococcal immune reconstitution inflammatory syndrome (IRIS) was conducted as a substudy of the Bacteriology and Mycology Study Group 3-01. Of 101 AIDS patients with cryptococcal meningitis who received highly active antiretroviral therapy (HAART), 13 experienced cryptococcal IRIS. No association between the timing of HAART initiation and the diagnosis of IRIS was identified. Increased baseline serum cryptococcal antigen (CrAg) titer was a risk factor for cryptococcal IRIS. © 2009 by the Infectious Diseases Society of America. All rights reserved.